Analysis of Product Quality of Rubber Production Using Six Sigma Method - Daryono (Universitas Tidar, 2024)
Contemporary companies function in a complex environment where opportunities are affordable, global markets are evolving faster than ever, and operational performance and organizational success are determined by customer-centric offerings. The motivation behind this study is to research what PT Surya's item quality means for the six sigma technique to distinguish factors that cause deformities and go to fitting lengths to work on the nature of their items. The assessment zeroed in only on the nature of elastic objects at PT Surya Teknologi Industri. Those expectations are called exceptional control. Inside the area of product development, the Six Sigma concept DMAIC (outline, measure, examine, improve and manipulate) is a method of approaches to enhance the technique that focuses on lowering operational changes and causes of failure. A non-public organisation referred to as PT. Surya Teknologi enterprise produces custom designs and plastic moulds. Consistent with the studies results, we are able to verify that the high-quality control done by way of the enterprise is good even above the sigma degree, however there are nonetheless many things that aren't true. We consider that the enterprise can improve the elements that cause defects and improve the great ofproducts produced.